A COMPREHENSIVE STUDY OF “ATTITUDES TOWARD COMMUNICATION SKILLS AMONG STUDENTS TEACHERS IN R.T.M.N.U ENGINEERING COLLEGES IN NAGPUR. - Prof shamina siddique (IJRDO - Journal of Social Science and Humanities Research, 2026)
The present study was carried out to determine the positive and negative attitudes among 289 students of class teachers using the communication skills attitude scale (CSAS) in RTMNU universities. GPA, year level of students were recorded. Overall results of study revealed that the mean of positive attitude score was 4.03. The mean of negative attitude scale score was 3.63. There were no significant differences between class teachers and childhood teachers students in their positive and negative attitudes toward communication skills. Students with grade point averages 2 and more have positive attitudes toward communication skills than students with grade point average less than 2. Senior students have high positive and less negative attitudes toward communication skills than sophomore and junior students.